Effect of Aerated Drinks on Force Decay Properties of Elastomeric Chains: An In Vitro Study - Kumar, Reena R; Gahlot, Mayank; Kaur, Nameeta; Miglani, Anil (Orthodontic Journal of Nepal, 2011)
Objective: To evaluate the effect of three commercially available aerated drinks on percentage of force decay of elastomeric chains used for orthodontic space closure. Materials & Method: Commercially available closed grey and clear elastomeric chains from two manufacturers were used in the study. The test solutions were distilled water (control), popular lemon based aerated drink, an orange based aerated drink and an aerated cola drink. Four acrylic resin jigs were constructed to provide a framework to simulate the distance between the permanent canine and first molar. The elastomeric chains were stretched and engaged between the two attachments. Jig I, II and III were immersed in the cola, orange and aerated lemon drink respectively for a period of two hours daily. Jig IV (control) was immersed in distilled water. Force levels were evaluated at the time intervals of 0 hours, 2 hrs, 12 hrs, 24 hrs, 3 days, 5 days and 7 days with a mechanical force gauge. Result: Force decay was statistically significant at T1 i.e. 2 hrs post immersion for all drinks compared. This decay was the highest for the elastomeric chains immersed in orange based drink followed by cola, lemon and the control. There was no significant difference between the two tested elastomeric chains. Conclusion: History recording should take cognizance of consumption of aerated drinks and their effect on orthodontic space closure.